Evidence-based interventions of threatened miscarriage - Juan Li (World Journal of Traditional Chinese Medicine, 2017)
Threatened miscarriage is the commonest complication of early pregnancy and affects about 20% of pregnancies. It presents with vaginal bleeding with or without abdominal cramps. Increasing age of women, smoking, obesity or polycystic ovary syndrome (PCOS) and a previous history of miscarriage are risk factors for threatened miscarriage. The pathophysiology has been associated with changes in levels of cytokines or maternal immune dysfunction. Clinical history and examination, maternal serum biochemistry and ultrasound findings are important to determine the treatment options and provide valuable information for the prognosis. Bed rest is the commonest advice, but there is little evidence of its value. Other options include progesterone, human chorionic gonadotropin (HCG) and muscle relaxants. The complementary and alternative medicine (CAM) therapies such as acupuncture and Chinese herbs have also been tried. There is some evidence from clinical studies indicating that CAM therapies may reduce the rate of miscarriage, but the quality of studies is poor. Thus, further double-blind, randomized-controlled trials are necessary to confirm its effectiveness, especially acupuncture and Chinese herbs.